Pengaruh kombinasi terapi akupunktur dan herbal kelor (moringa oliefera) terhadap penurunan nilai ambang nyeri pada kasus ischialgia di rsu Ja’far medika karanganyar - Jafar Maruf, Ibnu (STIKES Bethesda Yakkum, 2024)
Ischialgia is pain that radiates along the course of the sciatic nerve and its two branches, namely the common peroneal nerve & tibial nerve. This research is quantitative research, using an experimental research design, simple randomized the pretest-posttest control group design (RCT). The sampling technique used in this study was using simple random sampling technique. Research entitled